A numerical modeling approach for evaluation of spalling associated face instability in longwall workings under massive sandstone roof. (November 2020) - Behera, B.; Yadav, A.; Singh, G.S.P.; Sharma, S.K.
Highlights: The mechanism of face instability and associated spalling was studied. The critical strain limit of face instability was proposed. A design criteria was proposed for three-dimensional quantification of face spalling. Pertinent rock mechanics indicators of face spalling were comprehensively discussed. Abstract: The majority of the longwall panels in India have been worked underneath massive sandstone main roof with soft coal/shale immediate roof. As the mining goes deeper, ensuring stability and consistent production from such workings is a great challenge for their safety and sustainable performance. In this scenario, understanding the face instability mechanism and its rock mechanics precursors have evolved as a significant design challenge for obtaining an optimal longwall geometry in complex geo-mining conditions. Research to date mostly focused on the failure mechanism and, in some part, displacement characteristics of the coal wall. In contrast, minimal work has been performed to address the critical research gap from the face failure to spalling with the associated rock mechanics parameters and its three-dimensional quantification. This paper considered the longwall panel of 250 m face length and 3.5 m working height in the Godavari Valley Coalfield, which was worked underneath 23.5 m massive sandstone roof at a cover depth of 323 m. The finite difference software FLAC 3D was employed to investigate stress redistribution, failure characteristics, strain dynamics, and horizontal displacement of the coal wall until the occurrence of the main weighting. Accordingly, a set of criteria, namely, Percentage of Critically Strained Zone (PCSZ) and Percentage of Spalling Zones (PSZ), were proposed based on the critical limits of the lateral strain and the horizontal displacement of the face. The formation of these critical zones around the face was further correlated with the failure and caving characteristics of the massive sandstone roof. The study revealed that within 0–3 m distance ahead in the central region of the face, the extent of PCSZ in the Peak stress period was 46, which further enhanced and contributed in PSZ of 78 as noted during the weighting period. It is indicated that the impact of spalling dominated in the middle and the middle to the top portions of the face, covering 53% of total face length within 0–3 m regions ahead of the face. The relative influence of the failure and caving characteristics of the key roof positively correlated with the PCSZ and PSZ at the face. The critical limits of lateral strain (0.58%) and horizontal displacement (−15.40 mm), as projected in this study for evaluation of face instability, provided closer agreement with field observed extent of face spalling. The findings of the study supplements the existing knowledge about the mechanism of face spalling and its quantification in the Indian geo-mining conditions. The approach developed in this paper can be employed to analyze the extent of face instability during weighting periods.